Clinical significance of human epididymis protein 4 (HE4), cancer antigen 125 (CA125), the risk of ovarian malignancy algorithm (ROMA), and Copenhagen index (CPH-I) for the diagnosis of endometrial carcinoma - Vesselina Koleva; Sevim Shefket; Snezhana Stoencheva (Folia Medica)
Introduction: Endometrial carcinoma (EC) is the most common gynecological cancer among women, and in more than 90% of cases, the initial manifestation of the disease is postmenopausal bleeding. Unfortunately, despite early diagnosis and treatment, EC often recurs. Among the many serum tumor markers studied, human epididymis protein 4 (HE4) and cancer antigen 125 (CA125) show the most promise as tools for EC diagnosis, prognosis, and monitoring. Aim: The aim of the current study was to evaluate the clinical usefulness of HE4 and CA125, tested either as single markers or in combination by including them in the Risk of Ovarian Malignancy Algorithms (ROMA) and in Copenhagen index (CPH-I). Material and methods: In this retrospective study, 1262 women (74 with confirmed EC) were included. The patients with EC had significantly higher values for HE4, CA125, ROMA, and CPH-I (p<0.001) than the healthy women and patients with benign diseases. The subgroup analysis based on the histological type of EC revealed that the highest markers and algorithms were recorded in type II EC group. Results: The ROC curve analysis showed that the best diagnostic performance for detecting EC among patients with benign diseases was the ROMA index (AUC=0.869; 95% CI: 0.818-0.920), followed by CPH-I (AUC=0.822; 95% CI: 0.757-0.887), and HE4 (AUC=0.816; 95% CI: 0.750-0.881). Tested alone, CA125 presented unsatisfactory results for this purpose. Both algorithms proved to have a correlation with the disease stage and progression better than the markers alone (HR=1.046 vs. HR=1.018). Conclusion: In summary, the ROMA index, CPH-I, and, to a lesser extent, standalone HE4 testing can supplement imaging methods as reliable tools for diagnosing and distinguishing patients with EC from those with benign conditions. They have potential as prognostic markers for advanced disease and could help gynecological oncologists to develop a therapeutic strategy.